Why Do Household Portfolio Shares Rise in Wealth? - Wachter, Jessica A.; Yogo, Motohiro (Review of Financial Studies, 2010)
In the cross-section of U.S. households, the portfolio share in risky assets rises in wealth. The standard life-cycle model with power utility and non-tradable labor income has the counterfactual implication that the portfolio share declines in wealth. We develop a life-cycle model in which household utility depends on two types of consumption goods, basic and luxury. The model predicts that the expenditure share for basic goods declines in total consumption, and the variance of consumption growth rises in the level of consumption. When calibrated to match these two predictions in household consumption data, the model explains portfolio shares that rise in wealth. JEL classification: D11; D12; G11